2017
DOI: 10.1371/journal.pone.0182751
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cell markers are differentially expressed in the synovial tissue of patients with early arthritis

Abstract: IntroductionPrevious studies have shown increased expression of stromal markers in synovial tissue (ST) of patients with established rheumatoid arthritis (RA). Here, ST expression of stromal markers in early arthritis in relationship to diagnosis and prognostic outcome was studied.MethodsST from 56 patients included in two different early arthritis cohorts and 7 non-inflammatory controls was analysed using immunofluorescence to detect stromal markers CD55, CD248, fibroblast activation protein (FAP) and podopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 54 publications
3
35
0
Order By: Relevance
“…In this regard, we observed a strong upregulation of FAP and THY1 expression in Achilles’ tendons under voluntary running conditions, both in healthy as well as diseased mice (TNF ∆ARE ). A similar increase could also be observed in inflamed synovial tissue samples derived from patients with SpA, and to a lesser extent also in RA samples (online supplemental figure S9), in line with previous observations 25 28. The FAP and THY1 gene induction could also be directly linked to mechanical strain (online supplemental figure S11).…”
Section: Discussionsupporting
confidence: 88%
“…In this regard, we observed a strong upregulation of FAP and THY1 expression in Achilles’ tendons under voluntary running conditions, both in healthy as well as diseased mice (TNF ∆ARE ). A similar increase could also be observed in inflamed synovial tissue samples derived from patients with SpA, and to a lesser extent also in RA samples (online supplemental figure S9), in line with previous observations 25 28. The FAP and THY1 gene induction could also be directly linked to mechanical strain (online supplemental figure S11).…”
Section: Discussionsupporting
confidence: 88%
“…This was accompanied by reductions in synovial cellularity, joint damage, and leukocyte infiltration, highlighting that the changes observed were not solely due to a reduction in the number of cells within the synovium. Bulk-sequencing of sorted populations mirrored the findings of Zhang et al (41), with the largest differences being observed between the lining layer and sublining layer (45). Further similarities existed in the gene expression profile of these populations with the FAPα + CD90 + cells expressing higher levels of chemokines and cytokines, including IL-6, whereas the FAPα + CD90 − cells showed higher levels of RANKL and MMPs.…”
Section: Single Cell Approaches To Synovial Tissue Analysissupporting
confidence: 66%
“…Croft et al (42) used the serum transfer induced arthritis model in combination with the deletion of fibroblast activation protein-α (FAPα) expressing cells to interrogate the role of synovial fibroblast subsets. FAPα is expressed on both lining and sublining fibroblasts in RA, therefore offering a mechanism for the global deletion of synovial fibroblasts (42)(43)(44)(45). The deletion of FAPα + cells during arthritis led to both a significant reduction in inflammation and accelerated resolution.…”
Section: Single Cell Approaches To Synovial Tissue Analysismentioning
confidence: 99%
“…Furthermore, these biopsies do not appear to alter subsequent clinical or ultrasound disease activity assessments, which is important for patients who might subsequently enroll in clinical trials (73). These European groups have also performed numerous studies to validate the needle biopsy and portal and forceps procedures and tissue sampling (3436, 3840, 67, 74, 75). Our data demonstrate that the ultrasound-guided synovial tissue biopsies obtained from patients with RA are sufficient for RNA-seq, distinguish differences between patients with RA and OA, and importantly sets the framework for the stratification of patients with RA according to the most prominent disease pathway.…”
Section: Discussionmentioning
confidence: 99%